COST RISK'S RELIABILITY AND VALIDITY OF RESIDENTIAL BUILDING PROJECT'S WHOLE LIFE CYCLE IN THE UNITED ARAB EMIRATES - Sadek, Ahmed (Journal of Entrepreneurship and Project Management, 2021)
Purpose - Project management cost and risk modelling is experiencing the challenge of identifying cost risks values to maintain accurate modelling, estimating, and assessment. Latest research focused on cost and risk modelling and estimation. The significance of cost risks numerical values come from its ability to be used in many different analysis and approaches. This article aims to identify residential building projects' whole life cycle cost risks numerical values in UAE at the preconstruction stage and ensure its reliability and validity. Methodology - The approach of this research is pure quantitative. The methodology of this research is to collect data though conducting face-to-face interviews quantitatively (i.e., cost risks values). The survey is using PMBOK risk matrix (i.e., probability vs. impact). Finally, data correlation and regression modelling ware done to ensure the reliability and validity of each cost risk value. Findings - This paper was able to deliver reliable and valid residential project's whole life cycle cost risks values (i.e., 117 cost risks) for direct use in future research or practical professional cost analysis. Unique contribution to theory, practice and policy - This article contribution to the project management body of knowledge is to collect all relevant cost risks (i.e., 117 cost risks) and obtain their values from UAE field experts for the first time. The provided values are for residential project in UAE only. The perspective of how to look to cost risks values in this article (i.e., contractors' and clients' views) should be considered at the time of using the data. The consultancy services organizations will have different cost risks because they do not deal with delivering the final product, but they provide supporting services (i.e., design and supervision) to facilitate delivering the project.